Creation of the Pedagogy course at the Federal University of Mato Grosso do Sul (1980-1996) - Rodríguez, Margarita Victoria; Severino, Jorismary Lescano (Educação, Escola & Sociedade, 2020)
The article aims to analyze the Pedagogy course at the University of Mato Grosso do Sul, Campo Grande campus, specifically the creation and consolidation of the course between 1980 and 1996. The methodological procedures used include bibliographic and documentary research (laws, decrees, resolutions and opinions), also institutional sources (resolutions, opinions, statutes, minutes of meetings and annual report) from the 1970s, 1980s and 1990s. The proposal to start the Pedagogy course with qualification to work in pre-school and in the first years of elementary education it was unprecedented in the state of Mato Grosso do Sul, few institutions in Brazil trained teachers for this area. The creation of the course had as main objective to meet the demand of the state education network that needed trained professionals in higher education.